Computational investigation of the impact of assumption of affine deformation on constitutive models of soft tissues - Burša J.; Slažanský M. (Applied and Computational Mechanics, 2019)
All constitutive models proposed during the last decades for large strain composites with hyperelastic matrix use an intrinsic assumption of affine deformation between the matrix and reinforcing fibres. While for typical technical composites the affinity of deformation between fibres and matrix till high loads is ensured by targeted creation of their chemical bonds, this need not to be the case with soft biological tissues. For instance, this assumption might be disputable for arterial tissues with their matrix consisting of very compliant gel-like proteoglycans. On the other hand, no constitutive model proposed till now has been capable to give a reasonable fit of all mechanical tests of some pathological tissues with low initial stiffness, such as aortic aneurysm wall. Thus, a question occurs whether this discrepancy could not be caused by the intrinsic assumption of affine deformation used in all models. To test the impact of this assumption on the simulated response in some mechanical tests, two finite element models of specimens of arterial tissues were created, both including matrix and fibres separately. The former model mimicked the affine deformation of matrix and fibres by merging all the nodes of both components, while the deformation of fibres was independent of the matrix in the latter model, with exception of both fibre ends. Differences in reaction forces of specimens were evaluated in various strain states and directions with respect to the orientation of fibres. The evaluated differences between models with affine and non-affine deformations were significant but smaller than typical inaccuracies of constitutive models when fitting aortic aneurysm tissues.